The Risks of Adopting the Bond Yield as the Anchor for the EU Fiscal Framework - Fredrik N. G. Andersson; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2022)
The EU's fiscal rules, set out in the Maastricht Treaty of 1993 and the Stability and Growth Pact of 1997, are anchored to GDP. The debt ceiling and the deficit threshold are set to 60 percent and 3 percent of GDP, respectively. Recently, prominent economists and policymakers, have argued that that the debt ceiling should be raised due to falling bond yields. By extension, this argument suggests a shift from GDP anchoring to bond yield anchoring of the EU fiscal framework. We discuss the risks of basing the fiscal rules on the bond yield rather than on the GDP. While such a change would provide short-run relief to highly indebted EU member states, it implies high long-run risks to fiscal sustainability should bond yields rise in the future. We conclude that GDP serves as a better anchor for the EU fiscal framework than the bond rate under present circumstances.
Keywords: E50; E60; H60; N10; 330; Fiscal framework; European Union; ECB; Stability and Growth Pact; secular stagnation; modern monetary theory; government debt; fiscal policy